COVID-19 Pandemic and Its Effects on Household Income in Malaysia during Lockdown - Abdul Hadi, Azlina; Shahrol Nidzam, Nazirul Nazrin; Hamid, Mohamad Amin Hamid; Mohd Razali, Nornadiah (Journal of Statistical Modeling and Analytics (JOSMA), 2022)
The goal of this study is to identify the most vulnerable socioeconomic group of people to the effects of the pandemic as well as to examine the socioeconomic group that is more likely to be affected, in terms of income loss, by the pandemic. The data were collected via online questionnaire to the 395 respondents in Malaysia. The dependent variable involved in this study was income loss while the predicted variables included were age, gender, gross household income, employment sector, residential environment, education level and status of ‘Bantuan Sara Hidup’ (BSH) one-off relief. By employing Multinomial Logit Regression (MLoR) analysis via IBM SPSS Statistics 24, the most significant predictor is employment sector (P = 0.000), where those who are business owner, self-employed and unemployed are the most susceptible to the income loss due to COVID-19. The finding indicated those who own business or self-employed were 4.098 times more likely to have their income decrease (P = 0.002) while the unemployed respondents were 6.725 times more likely to have their income decrease (P = 0.014) rather than no changes in income during the COVID-19 outbreak.